Customer Relationship Management and Customer Value with Their Impacts On Consumer Satisfaction: A Literature View - Ni Nyoman Padang Cakra , Binaraesa (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The development of the times has led to market dynamics so that consumer expectations continue to increase so that a business strategy approach that focuses on customers is needed. Customer Relationship Management (CRM) and Customer Value can be used as the main tools to increase customer satisfaction while still adapting to environmental changes, such as dynamic customer desires. This study presents a review of previous literature that studies Customer Relationship Management and Customer Value and their impact on customer satisfaction through a literature study approach with qualitative descriptive analysis. This study reviews the 40 articles obtained and as many as 23 selected scientific articles about CRM and Customer Value which can affect consumer satisfaction, with a focus on the period 2018 to 2023. The results of this study are that having good relationships with customers and carried out in the long term, with apply the concept of Customer Relationship Management (CRM) and pay attention to Customer Value which will provide value to the benefits felt by consumers and will also have an impact on company profits by having satisfied customers to become loyal customers.